2012
DOI: 10.1016/j.immuni.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Excess Leads to Pathogenic Accumulation of Follicular Helper T Cells and Germinal Centers

Abstract: Overactivity of the germinal center (GC) pathway resulting from accumulation of follicular helper T (Tfh) cells causes autoimmunity, underscoring the need to understand the factors that control Tfh cell homeostasis. Here we have identifed posttranscriptional repression of interferon-γ (Ifng) mRNA as a mechanism to limit Tfh cell formation. By using the sanroque lupus model, we have shown that decreased Ifng mRNA decay caused excessive IFN-γ signaling in T cells and led to accumulation of Tfh cells, spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
209
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(226 citation statements)
references
References 61 publications
14
209
2
1
Order By: Relevance
“…TLR9/MyD88 signaling in DCs increased the magnitude of anti-NP IgG produced by promoting the expansion of T FH cells and GC B cells, whereas TLR9/MyD88 signaling in B cells primarily affected the quality of the GC response, resulting in better selection for high-affinity antibody, more class switching to IgG2a b , and a stronger secondary IgG response. Taken together, these data reveal that TLR9 signaling in multiple cell types cooperates to establish a coordinated GC reaction with characteristics previously demonstrated to be important in viral infection models, as well as in a mouse model of systemic lupus erythematosus (13,(41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 70%
“…TLR9/MyD88 signaling in DCs increased the magnitude of anti-NP IgG produced by promoting the expansion of T FH cells and GC B cells, whereas TLR9/MyD88 signaling in B cells primarily affected the quality of the GC response, resulting in better selection for high-affinity antibody, more class switching to IgG2a b , and a stronger secondary IgG response. Taken together, these data reveal that TLR9 signaling in multiple cell types cooperates to establish a coordinated GC reaction with characteristics previously demonstrated to be important in viral infection models, as well as in a mouse model of systemic lupus erythematosus (13,(41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, both IFN-g and IL-17 are important for the generation and maintenance of GCs during autoimmune reactions (61). Our findings revealed that S. Typhi porins induce not only IFN-g, but also an IL-17A response in CD4 + T cells, and that both Ifngr 2 and Il17ra deficiency impacts on GC and antiporin Ab generation.…”
Section: Discussionmentioning
confidence: 59%
“…However, it is possible that Tfh cells Our findings, in both TGF-βR-KO and TGF-βR-DN mice, indicated that T cells, either escaping or modulating TGF-β control, respectively, could accumulate spontaneously as Tfh cells. It is notable that these 2 mouse models have been associated with high levels of inflammatory cytokines such as IFN-γ (28, 49), which is known to lead to BCL6 overexpression and excessive development of Tfh cells (43). However, our work rules out any bystander cytokine action on Tfh cell population control in these mouse models, and thus underlines a direct effect of TGF-β on T cells to control Tfh cell homeostasis.…”
Section: Discussionmentioning
confidence: 74%